A DHT-Aided Chunk-Driven Overlay for Scalable and Efficient Peer-to-Peer Live Streaming - Shen, Haiying; Li, Ze; Li, Jin (IEEE transactions on parallel and distributed systems, 2013)
Internet-based video streaming applications are becoming more and more popular, attracting millions of online viewers every day. The incredible growth of viewers, dynamics of participants, and high video quality of service (QoS) requirement pose scalability, availability, and low-latency challenges to peer-to-peer (P2P) live video streaming systems. Tree-based systems have low-delay but are vulnerable to churn, while mesh-based systems are churn-resilient but suffer from high delay and overhead. Also, both structures cannot make full utilization of the bandwidth in the system. To tackle the challenges, we propose a DHT-aided chunk-driven overlay (DCO). It introduces a scalable DHT ring structure into a mesh-based overlay to efficiently manage video stream sharing. DCO includes a two-layer hierarchical DHT-based infrastructure, a chunk sharing algorithm, and a video provider selection algorithm. It selects stable nodes to form a scalable DHT-based infrastructure. The nodes in the DHT serve as distributed matchmakers between video providers and requesters. To motivate stable nodes to serve as the DHT nodes, we introduce an incentive mechanism based on the game theory. Aided by DHT, DCO guarantees stream chunk availability and assigns to a chunk requester a provider among all available providers in the system so that stream chunks are transmitted along a dynamic tree with top-down decreasing node bandwidth. In this way, DCO takes full advantage of available bandwidth in the system and, at the same time, provides high scalability and low latency. Experimental results show the superior performance of DCO compared with mesh-based and tree-based systems, and the effectiveness of the incentive mechanism and provider selection algorithm.